THE USE OF JOURNAL WRITING TO TEACH STUDENTS’ WRITING SKILL ON RECOUNT TEXT - Kalbarinda, Yesi; Regina, Regina; Wardah, Wardah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research was conducted to find out whether or not journal writing is effective to teach students writing skill on recount text. The writer used pre-experimental design. This research was conducted to the eighth grade students of SMPN 1 Manis Mata. The population was the students of class VIII with the total number of the students 172. The sample of this research was the students of class VIIIA which consists of 35 students. It was chosen by using cluster sampling technique. The technique used to collect the data was measurement technique with an essay written test as the tool of collecting data. The data were obtained from the result of pre-test and post-test. The mean score of pre-test was 57.82 and post-test was 61.25. The writer used t-test formula to find out the effectiveness of journal writing. From the calculation, the t-test was 3.3 which was higher than t-table (1.697) in df = 34 at level 0.05. The effect size was 0.55 which is categorized as moderate effect. The findings of the research obviously showed that the use of journal writing was significantly effective to teach writing recount text to the eighth grade students of SMPN 1 Manis Mata.Â Keywords: Writing, Recount Text, Journal Writing